Shifting Concerns: Punishment and Moral Decline in Puritan Essex County from 1636 to 1682 - Jed Pruett (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2011)
The second generation of Puritans in Massachusetts grew fearful for their future as their sons and daughters moved away from the strict morality of their parents. Historians have long accepted these fears as an accurate description of how morals changed in that period, pointing to the rise of mercantile, capitalist culture in late seventeenth century. This "declension model" helps us understand the general direction of changing morals and social patterns. By viewing changing legal sentencing for drunkenness and fornication from the 1630s to the 1680s as a window into the ethics of a community, we can see that this model only partially describes the moral trajectory of the community. Some of the religious and ethical decay that the older generation feared had long been present in Puritan culture.